Improving science learning outcomes through Youtube media for fifth grade students of SD Negeri 1 Sidamulih - Utami, Isti (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve student learning outcomes on the digestive system material of ruminant animals (cows). This research is a classroom action research (PTK) which was conducted in 3 cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were the fifth grade students of SD Negeri 1 Sidamulih, Rawalo District, Banyumas Regency in the academic year 2020/2021, totaling 28 students. Data collection techniques using observation, interviews, and tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the Youtube video media can improve student learning outcomes on the digestive system material for Ruminant Animals (Cows) in grade V SD Negeri 1 Sidamulih, Rawalo District, Banyumas Regency in the academic year 2020/2021 as evidenced by the percentage of completeness of learning outcomes in cycle I of 53.6 % to 92.9% in cycle III.